Total synthesis of Palmarumycin BGs, C1 and Guignardin E. Issue 3 (8th January 2020) - Liu, Xinlei; Li, Shuyi; Wei, Xinyu; Zhao, Yu; Lai, Daowan; Zhou, Ligang; Wang, Mingan
Abstract : The first total syntheses of Palmarumycin BG1–3, BG5–6, C1 and Guignardin E were achieved. These compounds displayed significant inhibition activities against HCT116, U87-MG, HepG2, BGC823 and PC9 cell lines. Abstract : The first total synthesis of Palmarumycin BG1–3, BG5–6, C1 and Guignardin E (1–7 ) were achieved by the same intermediate Palmarumycin C2 through a N -benzyl cinchoninium chloride-catalyzed epoxidation, an organoselenium-mediated reduction, and a cerium(iii ) chloride hydrate-promoted regioselective ring-opening and elimination of cyclic α, β-epoxy ketone as the key steps via 6–7 step routes using 1, 8-dihydroxynaphthalene (DHN) and 5-methoxytetralone as the starting materials in overall yields of 1.0–17.4%, respectively. Their structures and absolute configurations were characterized and determined by 1 H, 13 C NMR, IR, HR-ESI-MS and X-ray diffraction data. These compounds displayed significant inhibition activities against HCT116, U87-MG, HepG2, BGC823 and PC9 cell lines.